Deactivation of Excited States in Transition‐Metal Complexes: Insight from Computational Chemistry. Issue 5 (19th November 2018) - Sousa, Carmen; Alías, Marc; Domingo, Alex; de Graaf, Coen
Abstract: Investigation of the excited‐state decay dynamics of transition‐metal systems is a crucial step for the development of photoswitchable molecular based materials with applications in growing fields as energy conversion, data storage, or molecular devices. The photophysics of these systems is an entangled problem arising from the interplay of electronic and geometrical rearrangements that take place on a short time scale. Several factors play a role in the process: various electronic states of different spin and chemical character are involved, the system undergoes important structural variations and several nonradiative processes can occur. Computational chemistry is a useful tool to get insight into the microscopic description of the photophysics of these materials, since it provides unique information about the character of the electronic spin states involved, the energetics and time evolution of the system. In this review article, we present an overview of the state of the art methodologies available to address the several aspects that have to be incorporated to properly describe the deactivation of excited states in transition‐metal complexes. The most recent developments in theoretical methods are discussed and illustrated with examples. Abstract : Investigation of the excited‐state decay dynamics of transition‐metal systems is a crucial step for the development of photoswitchable molecular based materials with applications in growing fields as energy conversion, data storage, or molecular devices. An overview is presented of the state of the art methodologies available to address the several aspects that have to be incorporated to properly describe the deactivation of excited states in transition‐metal complexes.